2021
DOI: 10.3390/antibiotics10020113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Essential Oils from Cymbopogon spp. and Cinnamomum verum on Biofilm and Virulence Properties of Escherichia coli O157:H7

Abstract: Every year, the pharmaceutical and food industries produce over 1000 tons of essential oils (EOs) exploitable in different fields as the development of eco-friendly and safe antimicrobial inhibitors. In this work we investigated the potential of some EOs, namely Cinnamomum verum, Cymbopogon martini, Cymbopogoncitratus and Cymbopogon flexuosus, on the growth, biofilm formation and gene expression in four strains of enterohemorrhagic Escherichia coli O157:H7. All EOs were analyzed by gas chromatography-mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 58 publications
0
11
1
Order By: Relevance
“…In this regard, E. coli frequently leads to biofilm-associated opportunistic infections like endometritis, diarrhea, and mastitis ( Kim et al., 2017 ; Wang et al., 2020 ). Antibiotics can help alleviate disease symptoms and duration, but several E. coli species have developed resistance to antibiotics due to antibiotic overuse over the last 50 years ( Scotti et al., 2021 ). Hence, Cinnamomum was used to inhibit the attachment and formation of biofilms by E. coli to manage infection caused by this bacterium.…”
Section: Inhibitory Effects Of Cinnamomum On Micro...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, E. coli frequently leads to biofilm-associated opportunistic infections like endometritis, diarrhea, and mastitis ( Kim et al., 2017 ; Wang et al., 2020 ). Antibiotics can help alleviate disease symptoms and duration, but several E. coli species have developed resistance to antibiotics due to antibiotic overuse over the last 50 years ( Scotti et al., 2021 ). Hence, Cinnamomum was used to inhibit the attachment and formation of biofilms by E. coli to manage infection caused by this bacterium.…”
Section: Inhibitory Effects Of Cinnamomum On Micro...mentioning
confidence: 99%
“…To this end, the results of recent experimentation showed that C. verum essential oil (CVEO) inhibited the biofilm formation of EHEC clinical isolates. In addition, the microscopic examination revealed the following characteristics of biofilm cells in the presence of CVEO: sparse microcolonies and individual cells with fewer and shorter interconnecting meshes between cells, but no discernible morphological changes ( Scotti et al., 2021 ).…”
Section: Inhibitory Effects Of Cinnamomum On Micro...mentioning
confidence: 99%
“…et al, 2021). C. martini essential oil is also responsible for inhibiting several genes involved in the formation of E. coli O157:H7 biofilm (Scotti et al, 2021). Cinnamaldehyde was observed to prevent biofilm formation by Campylobacter spp.…”
Section: Essential Oilsmentioning
confidence: 96%
“…Thymol is also responsible for inhibiting P. aeruginosa biofilm by limiting the bacterial swimming and swarming motility (Liu et al, 2021). C. martini essential oil is also responsible for inhibiting several genes involved in the formation of E. coli O157:H7 biofilm (Scotti et al., 2021). Cinnamaldehyde was observed to prevent biofilm formation by Campylobacter spp.…”
Section: Plant‐based Substancesmentioning
confidence: 99%
See 1 more Smart Citation